2000
DOI: 10.1073/pnas.97.1.217
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in a NIMA-related kinase gene, Nek1 , cause pleiotropic effects including a progressive polycystic kidney disease in mice

Abstract: We previously have described a mouse model for polycystic kidney disease (PKD) caused by either of two mutations, kat or kat 2J , that map to the same locus on chromosome 8. The homozygous mutant animals have a latent onset, slowly progressing form of PKD with renal pathology similar to the human autosomal-dominant PKD. In addition, the mutant animals show pleiotropic effects that include facial dysmorphism, dwarfing, male sterility, anemia, and cystic choroid plexus. We previously fine-mapped the kat 2J mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
135
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(137 citation statements)
references
References 38 publications
1
135
0
1
Order By: Relevance
“…Instead, in both cases polycystic kidney disease is a major or the sole phenotype, respectively (Upadhya et al, 2000;Liu et al, 2002). Consistent with the polycystic kidney disease, localization of these proteins to the centrosome and to the primary cilium (Mahjoub et al, 2005;Shalom et al, 2008;White and Quarmby, 2008), and ciliary phenotypes (Smith et al, 2006;Shalom et al, 2008) have been reported.…”
Section: Introductionmentioning
confidence: 53%
“…Instead, in both cases polycystic kidney disease is a major or the sole phenotype, respectively (Upadhya et al, 2000;Liu et al, 2002). Consistent with the polycystic kidney disease, localization of these proteins to the centrosome and to the primary cilium (Mahjoub et al, 2005;Shalom et al, 2008;White and Quarmby, 2008), and ciliary phenotypes (Smith et al, 2006;Shalom et al, 2008) have been reported.…”
Section: Introductionmentioning
confidence: 53%
“…Some NRKs participate in ciliary functions (reviewed by Quarmby and Mahjoub, 2005). Mutations in the vertebrate NRKs, Nek1 and Nek8, cause polycystic kidney disease in mice and zebrafish (Upadhya et al, 2000;Liu et al, 2002). The FA2 gene of Chlamydomonas encodes an NRK that is essential for flagellar autotomy and normal rate of disassembly (Mahjoub et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Nek3 is a cytoplasmic protein relatively abundant at G 0 phase, but its function has not been established (13). Mutation in murine nek1 is involved in the Kat phenotype, including polycystic kidneys, dwarfism, male sterility, and facial dysmorphism (26), and nek4 is highly expressed in germinal cells similar to nek1 and nek2 (16,27,28), but functions of Nek1 and Nek4 are obscure. Nek6 and Nek7 are cytoplasmic proteins lacking the C-terminal regulatory domain (18) and function as putative regulators for p70 ribosomal S6 kinase (29).…”
mentioning
confidence: 99%